2011
DOI: 10.4274/turkderm.27676
|View full text |Cite
|
Sign up to set email alerts
|

Pemfigusta Risk Faktörleri

Abstract: ÖzetAmaç: Pemfigusun ortaya çıkmasında ve hastalığın seyrinde bazı dış faktörlerin etkili olduğu üzerinde durulmaktadır. Bu araştırma-da pemfigus tanısı ile takip ettiğimiz hastalarda hastalığın etyolojisinde rol oynayabilecek faktörlerin araştırılması amaçlanmıştır. Gereç ve yöntem: Kliniğimizde 1998-2004 yılları arasında histopatolojik ve direkt immunofloresan incelemeler ile pemfigus tanı-sı konan 15'i erkek, 27'si kadın toplam 42 hasta, demografik özellikler, meslek grubu, eğitim düzeyi, hastalığın ortaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…They reported that IVIG stopped the formation of bullous and epidermal detachment [7]. In addition, Tukenmez et al [8] reported IVIG therapy with positive results in two cases with TEN. In a multicenter study, Prins et al found that in the early period high-dose IVIG infusion was safe, well-tolerated and an effective treatment modality in cases with TEN [9].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that IVIG stopped the formation of bullous and epidermal detachment [7]. In addition, Tukenmez et al [8] reported IVIG therapy with positive results in two cases with TEN. In a multicenter study, Prins et al found that in the early period high-dose IVIG infusion was safe, well-tolerated and an effective treatment modality in cases with TEN [9].…”
Section: Discussionmentioning
confidence: 99%